An efficient electrochemical sensing of hazardous catechol and hydroquinone at direct green 6 decorated carbon paste electrode - K. Chetankumar; B. E. Kumara Swamy; S. C. Sharma; S. A. Hariprasad (Scientific Reports, 2021)
Abstract In this proposed work, direct green 6 (DG6) decorated carbon paste electrode (CPE) was fabricated for the efficient simultaneous and individual sensing of catechol (CA) and hydroquinone (HY). Electrochemical deeds of the CA and HY were carried out by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) at poly-DG6-modfied carbon paste electrode (Po-DG6-MCPE). Using scanning electron microscopy (SEM) studied the surface property of unmodified CPE (UCPE) and Po-DG6-MCPE. The decorated sensor displayed admirable electrocatalytic performance with fine stability, reproducibility, selectivity, low limit of detection (LLOD) for HY (0.11 μM) and CC (0.09 μM) and sensor process was originated to be adsorption-controlled phenomena. The Po-DG6-MCPE sensor exhibits well separated two peaks for HY and CA in CV and DPV analysis with potential difference of 0.098 V. Subsequently, the sensor was practically applied for the analysis in tap water and it consistent in-between for CA 93.25–100.16% and for HY 97.25–99.87% respectively.